2013
DOI: 10.1172/jci65401
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis of synaptic ADAM10 in neuronal plasticity and Alzheimer’s disease

Abstract: A disintegrin and metalloproteinase 10 (ADAM10), a disintegrin and metalloproteinase that resides in the postsynaptic densities (PSDs) of excitatory synapses, has previously been shown to limit β-amyloid peptide (Aβ) formation in Alzheimer's disease (AD). ADAM10 also plays a critical role in regulating functional membrane proteins at the synapse. Using human hippocampal homogenates, we found that ADAM10 removal from the plasma membrane was mediated by clathrin-dependent endocytosis. Additionally, we identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
89
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 68 publications
5
89
0
Order By: Relevance
“…Of note, ADAM9 and ADAM17 do not recover α-secretase proteolysis of APP in the absence of ADAM10 (5), neuron-specific overexpression of ADAM10 decreases Aβ load in a mouse model of AD (6), and impaired ADAM10 trafficking to the synapse generates a model of sporadic AD (7). Similarly, human studies have observed deficits in ADAM10 expression (8), trafficking (9), and activity (10) in AD. Therefore, dysregulation of ADAM10 may play a significant role in the establishment of Aβ pathology.…”
mentioning
confidence: 99%
“…Of note, ADAM9 and ADAM17 do not recover α-secretase proteolysis of APP in the absence of ADAM10 (5), neuron-specific overexpression of ADAM10 decreases Aβ load in a mouse model of AD (6), and impaired ADAM10 trafficking to the synapse generates a model of sporadic AD (7). Similarly, human studies have observed deficits in ADAM10 expression (8), trafficking (9), and activity (10) in AD. Therefore, dysregulation of ADAM10 may play a significant role in the establishment of Aβ pathology.…”
mentioning
confidence: 99%
“…In particular, we have identified an atypical AP2-binding motif in the ADAM10 C terminus, which is necessary for AP2 binding and ADAM10 internalization [14]. The lack of AP2 interaction significantly affects ADAM10 synaptic membrane levels, underlying the relevance of clathrin-mediated endocytosis in the modulation of ADAM10 surface expression.…”
mentioning
confidence: 99%
“…The samples were centrifuged in SW-bucket rotor at 60,000g for 90 min. According to the data of electron microscopy, highly purified synaptosomes were present in the layers 1.0 and 1.2 M. Collected portions were diluted ten times with Medium 1 and centrifuged in an fixed-angle rotor at 20,000g for APP within the Aβ domain, thus preventing generation of toxic Aβ peptide and therefore preventing Alzheimer disease [4,5].…”
Section: Isolation and Purification Of Synaptosomesmentioning
confidence: 99%
“…Compositionally simple peptides formed of five times repeated amino acid pairs (Lys-Phe) 5 and (Arg-Ala) 5 were incubated with purified axonal endings (synaptosomes) at 37 °C for 30 min (see "Materials and Methods"). Portions of the reaction medium (15 µl) were analyzed by TLC.…”
Section: Synaptosomes Possess Dipeptidase But Not Carnosinase Activitymentioning
confidence: 99%
See 1 more Smart Citation